Training Of Young Badminton Athletes With The Uniba Cup I Championship - Wawan Setiawan; Puji Setyaningsih; Lutfi Irawan Rahmat; Supono (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2020)
Badminton is in great demand by the community both as a daily sport and chosen to be a professional sport by many young Indonesians. It is proven by the large number of badminton athletes sprung up both at the regional and national level. All athletes involved in badminton have one goal, namely to make Indonesia famous in the world. With the slowness of the achievements of Indonesian athletes and to better maintain the competition of badminton achievements in the international arena, then we PGRI Banyuwangi University intends to hold a Badminton Championship SMA / SMK / MA throughout Besuki Raya "UNIBA Cup I 2020". Our hope with this badminton championship can bring quality badminton athletes to Indonesia in general. In this championship activity we as a committee provide a place for young badminton players to achieve again in the future and become a means of proving for them in measuring their ability to play badminton. In our service activities we carried out several stages including the preparatory stages including the socialization of the badminton championship by distributing invitation letters and championship brochures to SMA / SMK / MA throughout the Besuki residency. Next to record the players who have registered and the last is a technical meeting, after that the implementation stage of the championship is held for 5 days and the last is the final evaluation stage, namely making the final report. Based on the results of devotion activities that have been carried out, (1) players get the right place to maximize the player's psychology in competing and improve and measure the technical abilities possessed by players, (2) The trainer indirectly has a picture of how psychological conditions and abilities possessed by the players, so that they can determine the right formula in the next training program, (3) for the committee who are Penjaskesrek students, where they certainly get lessons in managing a championship and participate in the refereeing process.